Cultivated voices versus types of voices in the DDC: the use of metatheory for the understanding of the sung voice - Novaes, Fernanda Carolina Pegoraro [UNESP] (Univ Zaragoza, 2022)
Metatheory is used to identify and undestand the theories applied in the voice classification of the Dewey Decimal Classification (DDC). To this end, the following specific objectives were established: a) to carry out a bibliographic review on the meta-theory to understand it and apply it as a method in the present research; b) to investigate, through metatheory, the first classifications about voices in order to understand the theorys used by Music; c) compare and discuss the DDC voice classification from the perspective of the music theorys. It is concluded that the descriptions of voices from DDC start from the principle of music theory, but the way in which they are categorized disseminates pre-conceived ideas and is not supported by classification theory principles.
Keywords: Metatheory; Voice physiology; Cultivated voices; Voice types; Dewey Decimal Classification